Concepções de mães, pais e educadoras sobre desenvolvimento infantil e gênero - Vasconcelos, Dalila Castelliano (2017)
As of an early stage, interaction between adults and children is influenced by gender questions. This is a relevant aspect of infant development, once gender conceptions by adults may make it possible for girls and boys to hold different opportunities for development. In the first childhood, two major direct socializing contexts take part of the child’s life: the family, which is the primary socializing context, and the school. Considering child development from a cultural perspective, this research focuses on identifying and analyzing the conceptions by mothers, fathers, and educators of children aged two and three years old concerning infant development and gender relationships in childhood. As many as 40 mothers - 20 of whom of girls, and 20 of boys - 40 fathers, distributed similarly, and 20 educators - ten from children’s public educational centers, and ten from private ones. Data were analyzed with theoretical-methodological contributions from Bardin’s analysis content. Outcomes signal that the conceptions on infant development by the participants have an influence over caretaking strategies utilized, and over socialization goals presented by them. Mothers, fathers and educators describe boys and girls antagonistically, inasmuch as they state that girls are delicate, well-behaved, and enjoy girls’ plays, whereas boys are badlybehaved, active, agitated, and enjoy boys’ plays. A total of 65% of mothers and fathers, and 25% of educators asserted that they use sexist directives for interaction with girls. In relation to interaction with boys, this rate goes up to 95%, between mothers and fathers, and 65% between educators, which leads to the conclusion that boys undergo more interferences in their behavior than do the girls. The participants interfere with children’s actions and delimitate which exclusive activities suit each sex when they handle with opposite-sex typical toys and clothing items, and express behaviors most often accounted as usual for the opposite sex, too. Parents stated that they do not interfere in their children’s choice to play with children of the same sex, yet, by offering boys and girls distinct toys, besides providing a stereotype in the way of playing, they will also contribute for sexual segregation among children during plays. Such conceptions may be seen in intervention proposals targetting infant development promotion, and more equitable gender relationships.